(untitled) (Research, Society and Development, 2021)
Herbivore rabies, mainly disseminated by the hematophagous bat Desmodus rotundus, which transmits through the bite the virus Rhabdoviridae, is one of the most affected neurological diseases in the Brazilian cattle herd. However, this article aims to carry out a retrospective study of rabies in herbivores in the state of Rondônia, Brazil, evaluating the data provided by the health defense agency os state from 2009 to 2018, in this period of time. direct immunofluorescence tests 1,005 animals, 47 of them positive results, equivalent to about 4.7% of the total cattle verified. Over time, it became clear that the number of animals tested was decreasing along with the number of positive animals for pathology, where in 2009 there were 15 cases with 106 tests and already in the next 3 years with out of 321 tests resulted in only 10 confirmations. This demonstrates the effectiveness of application of the national herbivore rabies control program.